2005
DOI: 10.1038/nature03835
|View full text |Cite
|
Sign up to set email alerts
|

The ERECTA gene regulates plant transpiration efficiency in Arabidopsis

Abstract: Assimilation of carbon by plants incurs water costs. In the many parts of the world where water is in short supply, plant transpiration efficiency, the ratio of carbon fixation to water loss, is critical to plant survival, crop yield and vegetation dynamics. When challenged by variations in their environment, plants often seem to coordinate photosynthesis and transpiration, but significant genetic variation in transpiration efficiency has been identified both between and within species. This has allowed plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
426
3
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 513 publications
(472 citation statements)
references
References 24 publications
30
426
3
5
Order By: Relevance
“…The QTL with the largest effect on Δ 13 C explained more than 19% of the phenotypic variation. Although one study in Arabidopsis found a major QTL encoding the transcription factor, ERECTA, which explained up to 64% of the phenotypic variation in a Landsberg × Columbia RI population (Masle et al 2005), studies evaluating genetic variation for carbon isotope discrimination in other plant species have identified multiple QTLs of smaller effect associated with the trait. For example, in another population of Arabidopsis, two to five QTLs were identified Juenger et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The QTL with the largest effect on Δ 13 C explained more than 19% of the phenotypic variation. Although one study in Arabidopsis found a major QTL encoding the transcription factor, ERECTA, which explained up to 64% of the phenotypic variation in a Landsberg × Columbia RI population (Masle et al 2005), studies evaluating genetic variation for carbon isotope discrimination in other plant species have identified multiple QTLs of smaller effect associated with the trait. For example, in another population of Arabidopsis, two to five QTLs were identified Juenger et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the work on Arabidopsis by Masle et al (2005), the ERECTA gene underlying a Δ 13 C QTL was associated with both stomatal limitations on photosynthesis and leaf photosynthetic capacity at saturating CO 2 . In Arabidopsis, when two NILs were compared to the Landsberg erecta wild type, a significant difference in stomatal conductance (and transpiration efficiency) was associated with Δ 13 C QTLs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The d values were then converted to carbon isotopic discrimination values (D). The D value was calculated according to Masle et al (2005) …”
Section: Carbon Isotope Discriminationmentioning
confidence: 99%
“…Since these effects were observed close to midday, when irradiance levels were high, cry1 cry2 and phot1 phot2 could limit photosynthesis by lowering the flux of CO 2 . To investigate the long-term transpiration efficiency (CO 2 fixed/water loss ratio), the isotopic discrimination against 13 CO 2 with respect to 12 CO 2 (D; Farquhar and Richards, 1984;Masle et al, 2005) in plants grown under natural radiation was analyzed. The wild type and the cry1 cry2 and phot1 phot2 mutants presented similar D values (mean 6 SE in D per million, n = 3; the wild type, 22.1 6 0.1; cry1 cry2, 21.6 6 0.5; phot1 phot2, 21.8 6 0.4; P = 0.69), indicating that lower photosynthetic rates should accompany the lower transpiration rates presented by cry1 cry2 and phot1 phot2.…”
mentioning
confidence: 99%